Ultrasound-assisted extraction of capsaicinoids from capsicum frutescens (fruit) : laboratory scale to pilot scale - Sumate Boonkird (Chulalongkorn University, 2008)
Thesis (M.Eng.)--Chulalongkorn University, 2006